Extracellular matrix remodelling and stiffening contributes to tumorigenesis of salivary carcinoma ex pleomorphic adenoma——A study based on patient-derived organoids - Wanling Chen; Ting Gu; Qianqian Chen; Chuxiang Qu; Chunye Zhang; Yuhua Hu; Ronghui Xia; Ying Zhang; Min Wang; Xinyi Huang; Jiang Li; Chaoji Shi; et al. (Cell & Bioscience, 2023)
Abstract Background Salivary carcinoma ex pleomorphic adenoma (CXPA) is defined as a carcinoma that develops from benign pleomorphic adenoma (PA). Abnormally activated Androgen signaling pathway and amplification of HER-2/neu(ERBB-2) gene are known to be involved in CXPA tumorigenesis. Recent progress in tumour microenvironment research has led to identification that extracellular matrix (ECM) remodelling and increased stiffness act as critical contributing role in tumour carcinogenesis. This study examined ECM modifications to elucidate the mechanism underlying CXPA tumorigenesis. Results PA and CXPA organoids were successfully established. Histological observation, immunohistochemistry (IHC), and whole-exome sequencing demonstrated that organoids recapitulated phenotypic and molecular characteristics of their parental tumours. RNA-sequencing and bioinformatic analysis of organoids showed that differentially expressed genes are highly enriched in ECM-associated terms, implying that ECM alternations may be involved in carcinogenesis. Microscopical examination for surgical samples revealed that excessive hyalinized tissues were deposited in tumour during CXPA tumorigenesis. Transmission electron microscopy confirmed that these hyalinized tissues were tumour ECM in nature. Subsequently, examination by picrosirius red staining, liquid chromatography with tandem mass spectrometry, and cross-linking analysis indicated that tumour ECM was predominantly composed of type I collagen fibers, with dense collagen alignment and an increased level of collagen cross-linking. IHC revealed the overexpression of COL1A1 protein and collagen-synthesis-related genes, DCN and IGFBP5 (p < 0.05). Higher stiffness of CXPA than PA was demonstrated by atomic force microscopy and elastic imaging analysis. We utilized hydrogels to mimic ECM with varying stiffness degrees in vitro. Compared with softer matrices (5Kpa), CXPA cell line and PA primary cells exhibited more proliferative and invasive phenotypes in stiffer matrices (50Kpa, p < 0.01). Protein-protein interaction (PPI) analysis of RNA-sequencing data revealed that AR and ERBB-2 expression was associated with TWIST1. Moreover, surgical specimens demonstrated a higher TWIST1 expression in CXPA over PA. After knocking down TWIST1 in CXPA cells, cell proliferation, migration, and invasiveness were significantly inhibited (p < 0.01). Conclusion Developing CXPA organoids provides a useful model for cancer biology research and drug screening. ECM remodelling, attributed to overproduction of collagen, alternation of collagen alignment, and increased cross-linking, leads to increased ECM stiffness. ECM modification is an important contributor in CXPA tumorigenesis.